Respuesta :

In functions; transformations are used to move lines, points, curves or shapes across the graph (i.e. up, down, right or left). After the transformation of [tex]f(x) = \log\ x[/tex], the resulting function is [tex]g(x) = 2\log\ (-x + 4) - 6[/tex]

Given that:

[tex]f(x) = \log\ x[/tex]

When translated 4 units left, the rule of translation is:

[tex](x,y) \to (x + 4,y)[/tex]

So, we have:

[tex]f'(x) = \log\ (x + 4)[/tex]

When translated 3 units down, the rule of translation is:

[tex](x,y) \to (x,y-3)[/tex]

So, we have:

[tex]f"(x) = \log\ (x + 4) - 3[/tex]

When reflected about the y-axis, the rule of reflection is:

[tex](x,y) \to (-x,y)[/tex]

So, we have:

[tex]f'"(x) = \log\ (-x + 4) - 3\\[/tex]

Lastly, when it is vertically stretched by 2; the rule is:

[tex](x,y) \to (x,2y)[/tex]

So, we have:

[tex]g(x) = 2[\log\ (-x + 4) - 3][/tex]

Open bracket

[tex]g(x) = 2\log\ (-x + 4) - 6[/tex]

See attachment for the graph of function f(x) and the new function g(x)

Read more about function transformations at:

https://brainly.com/question/24369847

Ver imagen MrRoyal